The nervous conditions of neo-liberated HE students - van Zyl, Gerhard (South African Journal of Higher Education, 2016)
It is election year 2014. To the newly liberated a higher education (HE) qualification in 1994 represented both a means to a prosperous end, and a hope-filled end in itself. Whichever party manages to achieve political victory two decades later, the current South African HE situation remains one that requires critical thought and accurately applied resources from both victors and others, because in failed HE there can be no victors. HE fails when an abnormally high number of students either fail or withdraw prematurely and involuntarily for financial or other reasons. This article aims to redefine the higher education mainstream by presenting a window into the hope-taken, hope-lost, hope-deprived and hope-terminated realities inhabiting the real-life situations of a particular body of tertiary students; their nervous condition. The majority of black (by inclusive definition)students of transforming HE institutions hail from a despairing socio-economic context. Desperation and deprivation define the neo-mainstream. Universities embarking on a hope-generating road are likely to terminate that same hope should they remain either ill-informed about, or non-sympathetic towards the real-life situations of their neo-mainstream students, and inaccurate in their support programmes. This article aims to inform. Keywords: higher education; throughput; mainstream; support; real-life situations; nervous conditions